Slow-oscillatory transcranial direct current stimulation can induce bidirectional shifts in motor cortical excitability in awake humans - Groppa, S.; Bergmann, T.O.; Siems, C.; Mölle, M.; Marshall, L.; Siebner, H.R. (Neuroscience, 2010)
Constant transcranial direct stimulation (c-tDCS) of the primary motor hand area (M1 HAND) can induce bidirectional shifts in motor cortical excitability depending on the polarity of tDCS. Recently, anodal slow oscillation stimulation at a frequency of 0.75 Hz has been shown to augment intrinsic slow oscillations during sleep and theta oscillations during wakefulness. To embed this new type of stimulation into the existing tDCS literature, we aimed to characterize the after effects of slowly oscillating stimulation (so-tDCS) on M1 HAND excitability and to compare them to those of c-tDCS. Here we show that so-tDCS at 0.8 Hz can also induce lasting changes in corticospinal excitability during wakefulness. Experiment 1. In 10 healthy awake individuals, we applied c-tDCS or so-tDCS to left M1 HAND on separate days. Each tDCS protocol lasted for 10 min. Measurements of motor evoked potentials (MEPs) confirmed previous work showing that anodal c-tDCS at an intensity of 0.75 mA (maximal current density 0.0625 mA/cm2) enhanced corticospinal excitability, while cathodal c-tDCS at 0.75 mA reduced it. The polarity-specific shifts in excitability persisted for at least 20 min after c-tDCS. Using a peak current intensity of 0.75 mA, neither anodal nor cathodal so-tDCS had consistent effects on corticospinal excitability. Experiment 2. In a separate group of ten individuals, peak current intensity of so-tDCS was raised to 1.5 mA (maximal current density 0.125 mA/cm2) to match the total amount of current applied with so-tDCS to the amount of current that had been applied with c-tDCS at 0.75 mA in Experiment 1. At peak intensity of 1.5 mA, anodal and cathodal so-tDCS produced bidirectional changes in corticospinal excitability comparable to the after effects that had been observed after c-tDCS at 0.75 mA in Experiment 1. The results show that so-tDCS can induce bidirectional shifts in corticospinal excitability in a similar fashion as c-tDCS if the total amount of applied current during the tDCS session is matched.